A Systematic Review of the experimental induction of auditory perceptual experiences. (June 2021) - Anderson, Amanda; Hartley, Samantha; Bucci, Sandra
Abstract: Background and objectives: Voice-hearing exists on a continuum and research studies have utilised experimental paradigms in an attempt to induce unusual auditory experiences in clinical and non-clinical samples. The aim of the current review was to systematically identify, review and appraise voice-hearing induction paradigms in order to guide researchers. Methods: Five databases were searched for studies in which an experimental manipulation was used with the aim of inducing an auditory experience akin to voice-hearing. Papers were assessed for quality and the voice-hearing paradigms critically appraised. Results: Forty-nine studies, included in 41 papers, were reviewed. Studies were organised into five groups based on the type of voice-hearing paradigm used: sensory deprivation/limitation; hallucination suggestion; combined suggestion and ambiguous stimulus; signal detection and voice detection tasks; and auditory discrimination/transformation. Signal and voice detection tasks were found to be the most robust paradigms. The quality of paradigms was assessed, and their strengths and limitations evaluated, including evidence in relation to their utility, ecological validity and usability. Limitations: The current review excluded case studies, grey literature and studies which were not written in the English language, and as such voice-hearing paradigms may have been missed. Conclusions: Voice-hearing paradigms vary in their ecological validity and experimental robustness. A challenge for future research is to develop a paradigm in which internally generated material can be attributed externally in a way that more closely represents inner speech and the experience of voice-hearing. Highlights: There are broadly five groups of voice-hearing paradigms. Signal and voice detection tasks were found to be the most robust. Paradigms should seek to reflect both experimental validity and clinical experience.